Sol-gel fabrication and samarium doping of ferroelectric BiFeO3 thin films - Loh, Joel Yi Yang. (2010)
Bismuth Ferrite (BFO) thin films of ~200nm were fabricated via a sol-gel spin coating method. Troubleshooting of the recipe proved partially successful in obtaining BFO samples with low density of defects. Hence leakage current remains high in the BFO samples and good hysteresis loops could not be obtained. Doping of Sm did not manage to reduce the leakage current sufficiently to obtain good measurements either. Only via a higher frequency input voltage pulse of 10KHz, were we able to obtain values of the coercive field and remnant polarization of ~200nm BFO samples. The coercive fields obtained (380-550kV/cm) were in agreement with literature values (400-450kV/cm), but the remnant polarization (~50kV/cm2) was much smaller than literature values (70-150 kV/cm2). PFM images show that BFO samples were indeed ferroelectric with domains of random size; square hysteresis and strain butterfly loops were also obtained. Further work needs to be done to improve the quality of BFO samples in order to reduce the magnitude of leakage current during probe station testing.